A Review of the Diagnosis and Treatment of Atlantoaxial Dislocations. (August 2014) - Yang, Sun Y.; Boniello, Anthony J.; Poorman, Caroline E.; Chang, Andy L.; Wang, Shenglin; Passias, Peter G.
Study Design: Literature review. Objective: Atlantoaxial dislocation (AAD) is a rare and potentially fatal disturbance to the normal occipital-cervical anatomy that affects some populations disproportionately, which may cause permanent neurologic deficits or sagittal deformity if not treated in a timely and appropriate manner. Currently, there is a lack of consensus among surgeons on the best approach to diagnose, characterize, and treat this condition. The objective of this review is to provide a comprehensive review of the literature to identify timely and effective diagnostic techniques and treatment modalities of AAD. Methods: This review examined all articles published concerning "atlantoaxial dislocation" or "atlantoaxial subluxation" on the PubMed database. We included 112 articles published between 1966 and 2014. Results: Results of these studies are summarized primarily as defining AAD, the normal anatomy, etiology of dislocation, clinical presentation, diagnostic techniques, classification, and recommendations for timely treatment modalities. Conclusions: The Wang Classification System provides a practical means to diagnose and treat AAD. However, future research is required to identify the most salient intervention component or combination of components that lead to the best outcomes.